Where is the patriarchy?: A review and research agenda for the concept of patriarchy in management and organization studies - Ferry, Nicole (Gender, work, and organization, 2025)
In this paper I analyze 30 years of research on patriarchy in top management and organization studies (MOS) journals, and I map out an agenda for (re)igniting patriarchy as both a topic of study and lens for viewing key MOS issues in a new light. I organize my review (175 articles) around three themes: intersections, subjects, and contexts. By intersections I refer to the nuanced ways that scholars define patriarchy, adopting interdisciplinary and intersectional perspectives to understand the diversity of women's experiences under patriarchal domination. By subjects I refer to the primary focus on women's experiences, and on the ways that women's subjectivities are socially constituted and negotiated within patriarchal discourses of work and organizational life. By contexts I refer to the sites where MOS research has investigated patriarchy, as well as the ways this research has framed patriarchy itself as a context. Based on this thematic review, I outline a future research agenda to further refine the concept in MOS in three key ways. I call for increased research approaches that center the structural/political forces of patriarchy and gender, increased focus on the experiences of men as agents and subjects of patriarchal domination, and increased attention on patriarchy in Western contexts to redress the overrepresentation of research on patriarchy in the Global South. I conclude that patriarchy is an important line of inquiry for MOS, and that further attention to the concept would enable MOS research to contribute more fully to contemporary debates on gender.